2022
DOI: 10.3389/feduc.2022.838938
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver-Reported Changes in the Socioemotional Wellbeing and Daily Habits of Children With Special Educational Needs During the First COVID-19 National Lockdown in the United Kingdom

Abstract: The implementation of social distancing measures (e.g., school closures) by governments worldwide to prevent the spread of COVID-19 has affected millions of children and their families. However, the consequences of such measures on the wellbeing of children with special educational needs (SEN) and their caregivers are not fully understood. The present study examined the socioemotional wellbeing and daily habits of children between 5 and 12 years old with SEN during the first national COVID-19 lockdown in the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…Several studies identified that children with SEN experienced greater social isolation, whether assessed by parent or teacher perception (Castro‐Kemp & Mahmud, 2021; Page et al, 2021), as compared with children without SEN. Similar findings have been reported among a variety of other countries including Germany, India, the Philippines, and the United Kingdom (Buendia, 2021; Morgül et al, 2022; Nusser, 2021; Page et al, 2021). German participants in a study by Nusser (2021) reported challenges during school closures relating to low student motivation and increased demands.…”
Section: Introductionsupporting
confidence: 81%
“…Several studies identified that children with SEN experienced greater social isolation, whether assessed by parent or teacher perception (Castro‐Kemp & Mahmud, 2021; Page et al, 2021), as compared with children without SEN. Similar findings have been reported among a variety of other countries including Germany, India, the Philippines, and the United Kingdom (Buendia, 2021; Morgül et al, 2022; Nusser, 2021; Page et al, 2021). German participants in a study by Nusser (2021) reported challenges during school closures relating to low student motivation and increased demands.…”
Section: Introductionsupporting
confidence: 81%
“…For the minimally increasing distress, the presence of family conflict was the only predictor of membership to this trajectory. Some studies have reported increases in family conflict during lockdown periods (Morgül, Kallitsoglou, Essau, & Castro‐Kemp, 2022 ; Orgilés et al., 2020 ; Stassart et al., 2021 ). In a longitudinal study with adolescents, family conflict was associated with larger increases in distress over time (Magson et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, interpersonal stress may contribute to aggravate psychological distress under stressful conditions (Hammen, 2016 ). In particular, studies have provided some evidence of increased family conflict during lockdowns (Guo et al., 2020 ; Morgül, Kallitsoglou, Essau, Castro‐kemp, & Mateo, 2022 ). These family conflict, resulting from a wide range of stressors affecting family members, such as work from home/teleworking, loss of income, home‐schooling, and movement restrictions for young people to meet up with their friends, could increase risk for adolescents' psychological distress.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, families experiencing vulnerabilities (e.g., families with children with special educational needs or disabilities) were more likely to be adversely affected by lockdown measures. Families experienced difficulties accessing social support and children with mental health difficulties were reported to struggle more behaviourally and emotionally than their peers during lockdown, and parents of these children experienced higher than usual levels of stress [8,9].…”
Section: Introductionmentioning
confidence: 99%